2006
DOI: 10.1074/jbc.m606360200
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Small Chlorophyll-binding Protein ScpD (HliB) Is Located on the Periphery of Photosystem II in the Vicinity of PsbH and CP47 Subunits

Abstract: Cyanobacteria contain several genes coding for small one-helix proteins called SCPs or HLIPs with significant sequence similarity to chlorophyll a/b-binding proteins. To localize one of these proteins, ScpD, in the cells of the cyanobacterium Synechocystis sp. PCC 6803, we constructed several mutants in which ScpD was expressed as a His-tagged protein (ScpDHis). Using two-dimensional native-SDS electrophoresis of thylakoid membranes or isolated Photosystem II (PSII), we determined that after high-light treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 65 publications
5
54
2
Order By: Relevance
“…In this respect, it is interesting that the level of Psb28 is significantly decreased in the mutant lacking the PsbH protein (Fig. 3A), which was previously shown to be essential for the binding of Hli proteins to CP47 (Promnares et al, 2006). We therefore assume that the Psb28 binding site on CP47 is located in the vicinity of PsbH.…”
Section: Role Of Psb28 In the Structure And Function Of Psiimentioning
confidence: 93%
See 1 more Smart Citation
“…In this respect, it is interesting that the level of Psb28 is significantly decreased in the mutant lacking the PsbH protein (Fig. 3A), which was previously shown to be essential for the binding of Hli proteins to CP47 (Promnares et al, 2006). We therefore assume that the Psb28 binding site on CP47 is located in the vicinity of PsbH.…”
Section: Role Of Psb28 In the Structure And Function Of Psiimentioning
confidence: 93%
“…7). Recent results showing the association of so-called high light-induced proteins with PSII (Promnares et al, 2006;Yao et al, 2007) and their presumable role in the temporary binding of Chl during the PSII repair-related D1 replacement (Vavilin et al, 2007) indicate that Chl molecules released from the degraded D1 can be reused. It is possible that the lack of the newly synthesized CP47 allows more Chl precursors to be utilized for the synthesis of Chl consumed during selective D1 turnover.…”
Section: Role Of Psb28 Protein In the Synthesis Of Chl And Chl-bindinmentioning
confidence: 99%
“…Deletion of the ferrochelatase CAB domain resulted in an aberrant accumulation of chlorophyll-protein complexes under high light, a phenotype not observed for other Hlip mutants (Sobotka et al, 2011). HliA, HliB, and HliC were found to interact with the PSII subunit CP47, likely to photoprotect the PSII assembly machinery and stabilize chlorophylls released during the process of PSII repair (Promnares et al, 2006;Yao et al, 2007). In contrast, HliD does not colocalize with PSII (Yao et al, 2007) but rather, as shown in this work, HliD copurifies with FLAG-ChlG (Figure 1).…”
Section: The Hlid Componentmentioning
confidence: 99%
“…This protein family, also called small cab-like proteins, aids in high-light survival and photoacclimation in Synechocystis (He et al, 2001;Havaux et al, 2003), and may also have a role in light-shock tolerance in eNATL. The mechanism by which they do this remains unclear, but high light-inducible proteins are thought to physically associate with either photosystem and allow it to shed excess energy as heat and thereby reduce photoinactivation (Promnares et al, 2006;Yao et al, 2007). As a photosynthetic organism, reducing and reversing the effects of photosystem inactivation is crucial for the survival of Prochlorococcus exposed to high light levels.…”
Section: Response To Light Shock In Cultured Isolatesmentioning
confidence: 99%